2006
DOI: 10.3310/hta10210
|View full text |Cite
|
Sign up to set email alerts
|

Health benefits of antiviral therapy for mild chronic hepatitis C: randomised controlled trial and economic evaluation

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
198
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(206 citation statements)
references
References 94 publications
4
198
0
4
Order By: Relevance
“…Wright et al 414 were unable to locate separate estimates of probabilities of progression from mild to moderate fibrosis disease stages health state from existing studies as they found that most data were based on retrospective natural history studies which do not use liver biopsy to stage fibrosis and progression. As the disease progression may not be linear, it may not be realistic to assume a constant rate of progression from mild fibrosis to cirrhosis, and so they estimated transition probabilities for mild and moderate health states using data from a trial of treatments for mild HCV undertaken in a number of London hospitals, 415 during which the liver fibrosis stage was determined by liver biopsy.…”
Section: Cost-effectiveness Analysis: Hepatitis Bmentioning
confidence: 99%
See 3 more Smart Citations
“…Wright et al 414 were unable to locate separate estimates of probabilities of progression from mild to moderate fibrosis disease stages health state from existing studies as they found that most data were based on retrospective natural history studies which do not use liver biopsy to stage fibrosis and progression. As the disease progression may not be linear, it may not be realistic to assume a constant rate of progression from mild fibrosis to cirrhosis, and so they estimated transition probabilities for mild and moderate health states using data from a trial of treatments for mild HCV undertaken in a number of London hospitals, 415 during which the liver fibrosis stage was determined by liver biopsy.…”
Section: Cost-effectiveness Analysis: Hepatitis Bmentioning
confidence: 99%
“…Resource use data on blood products used, number of dietitian sessions, drugs used, inpatient stay, nutritional support received, outpatient visits, physiotherapy sessions, tests, length of transplant operation and key treatments and investigations were collected. Based on the review, we concluded that the data on costs for treating HCV from the study by Wright et al 414 for the mild, moderate and cirrhotic health states would be comparable with the costs for treating patients with HBV in these health states, as the resource use identified and collected (inpatient, outpatient care, procedures) should be similar. The health state costs sourced from this study did not contain the cost of antiviral treatment; therefore, they were suitable to use and we added the cost of treatment separately in the model.…”
Section: Cost Datamentioning
confidence: 99%
See 2 more Smart Citations
“…For parameters in which there were no UK-based studies available, we sought data from countries with a similar disease profile. Cost data were obtained from national (UK NHS; Department of Health (DoH), 2005) sources where available, supplemented by data from a recent UK-based observational study of patients with HCV (Wright et al, 2006). Historical values were inflated to 2004 prices.…”
Section: Parametersmentioning
confidence: 99%